2021
DOI: 10.1021/acs.jafc.1c00550
|View full text |Cite
|
Sign up to set email alerts
|

Selective Action Mechanism of Fenclorim on Rice and Echinochloa crusgalli Is Associated with the Inducibility of Detoxifying Enzyme Activities and Antioxidative Defense

Abstract: Fenclorim (Fen) is a safener developed for pretilachlor (Pre) that can protect rice from injury caused by Pre but does not lower the weed control effects of Pre. Unfortunately, the mechanism of selective action of Fen between rice and weeds, such as Echinochloa crusgalli (barnyard grass), has not been clarified. In this study, the differences in physiology, biochemistry, and gene transcription between rice and E. crusgalli response to Fen were compared. Comparing the protection effects of Fen on plant growth, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 29 publications
0
17
0
Order By: Relevance
“…48 In addition, the GST activity analysis showed that fenclorim increased the activity of rice instead of E. crus-galli. 48 Some studies have already reported the risk to select resistant weed biotypes applying herbicide safeners. Cloquintocet-mexyl and mefenpyr-diethyl reduced Agrostis stolonifera injury from pinoxaden, but also reduced efficacy against Poa trivialis, and did not affect Lolium perenne control.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…48 In addition, the GST activity analysis showed that fenclorim increased the activity of rice instead of E. crus-galli. 48 Some studies have already reported the risk to select resistant weed biotypes applying herbicide safeners. Cloquintocet-mexyl and mefenpyr-diethyl reduced Agrostis stolonifera injury from pinoxaden, but also reduced efficacy against Poa trivialis, and did not affect Lolium perenne control.…”
Section: Discussionmentioning
confidence: 99%
“…48 The transcriptome analysis showed that fenclorim up-regulated six GST genes in rice, while it down-regulated four GST genes in E. crus-galli. 48 In addition, the GST activity analysis showed that fenclorim increased the activity of rice instead of E. crus-galli. 48 Some studies have already reported the risk to select resistant weed biotypes applying herbicide safeners.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Herbicides are an efficient tool in modern agriculture and effectively control weeds in the crop field [11,12]. Generally, herbicides have a specific site of action that kills weeds by selecting the potential molecular target.…”
Section: Introductionmentioning
confidence: 99%